Does diet quality mediate socioeconomic differences in metabolic syndrome in the French West Indies?. (13th November 2019) - Colombet, Z; Perignon, M; Salanave, B; Landais, E; Martin-Prével, Y; Allès, B; Drogue, S; Amiot-Carlin, M-J; Méjean, C
Abstract: Background: Obesity and metabolic diseases represent a major health burden in the Caribbean, particularly since a large part of the population is disadvantaged. However, socioeconomic inequalities in chronic diseases are poorly explored in this region, and the contribution of diet to explain these inequalities has not yet been studied. We investigated the association between socioeconomic position and the prevalence of metabolic syndrome (MetS), and explored whether this association was mediated by diet quality in the French West Indies. Methods: This cross-sectional analysis included 1, 144 adults (≥16 y) from a multistage sampling survey, representative of the Guadeloupean and Martinican population. The prevalence of MetS was assessed using the Joint Interim Statement. Dietary intakes were estimated using 24hours dietary recalls, and diet quality was assessed through the Diet Quality Index-International (DQI-I). Associations between socioeconomic indicators (education, employment, social assistance benefits) and prevalence of MetS, and the potential mediating effect of diet quality in this association were assessed using multivariable logistic regression models adjusted for sociodemographic factors. Results: MetS prevalence adjusted for age and sex was 21% and 30% among Guadeloupean and Martinican, respectively. Compared to those with a high education level, low- and middle-educated subjects were more likely to be at risk of MetS (OR = 1.9; 95%CI = [1.0-3.6] and OR = 2.7; 95%CI = [1.4-5.1], respectively), as were recipients of social assistance benefits compared to non-recipients (OR = 2.2; 95%CI = [1.1-4.2]). The DQI-I explained 11% of the overall variation in MetS due to education. Conclusions: Socioeconomic inequalities in MetS prevalence were found in a Caribbean population but diet quality contributed only to socioeconomic inequalities due to education. Future public health measures need to target specifically populations with limited financial resources and low education. Key messages: Our work identified subgroups with higher risk of MetS, which is needed when implementing public health measures, particularly in this Caribbean population with of high poverty rates. Diet quality contributed only to socioeconomic inequalities due to education underlining that education may impact health through the ability to generate overall dietary behavior, long-term beneficial.